Examining the Correlation between Explosive Power and Endurance in State-Level Cricketers: A Performance Analysis - Saini , Preeti (Contemporary Perspective on Science, Technology and Research Vol. 4, 2024)
Background: Cricket, often classified as an aerobic sport, involves players engaging in diverse activities at varying intensities and speeds, such as jumping, sprinting, catching, and diving. Despite being interspersed with intervals, the game demands bursts of explosive actions, making it crucial to explore the association between explosive power and endurance in state-level cricketers. This study aims to fill the gap in the literature by investigating the correlation between these physical attributes, considering the limited evidence on this topic. Methods: Conducted in Faridabad, this study involved 100 male state-level cricketers aged 16-23 from various cricket academies. A thorough screening and assessment protocol was employed for participant selection, with performance tests measuring explosive power through the vertical jump test and endurance using the yo-yo intermittent recovery test. Results: The study unveiled a significant positive correlation (r = 0.237, p = 0.017) between explosive power and VO2 max levels in state-level cricketers. Conclusion: The findings suggest that there is a positive association between explosive power and V02 max levels among state-level cricketers, emphasizing the importance of addressing both aspects in their training regimes.